Efektivitas Pembelajaran Konstruktivis dengan Model Siklus Belajar Terhadap Aktivitas dan Ketercapaian KKM Mata Pelajaran Bahasa Inggris Siswa Kelas XI ATPH SMK Negeri 1 Woja - Nurdewiyati (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2020)
The purpose of this study was to determine the effectiveness of constructivist learning with a learning cycle model of student activities in English subjects for class XI students of ATPH SMK Negeri 1 Woja in the academic year 2018/2019. The method used in this research is descriptive qualitative. The research subjects were students of class XI ATPH SMK Negeri 1 Woja in the 2018/2019 school year. Data used are the results of test results, and interviews. The results showed that the brainstorming activity could improve students' skills in using acceptable spoken English specifically to express descriptive monologues. Evidence from quantitative data analysis shows that the value of student learning outcomes, in general, is above the English Minimum Mastery Criteria (KKM) of 70.